Growth Mindset Pedagogy (GMP) in Basic Calculus Learners’ Material - Suarez, Diana Rose D.; Villapando, Melchor A. (Edukhasi: Jurnal Inovasi Pendidikan, 2025)
The main purpose of this study is to examine the challenges and successes of implementing a growth mindset in basic calculus. It aimed to identify the influence of a growth mindset on students' passion, grit, and overall learning experience using quantitative and qualitative approaches. The explanatory-sequential mixed methods design was utilized. Selected grade 11 senior high school students under the STEM strand at STI College Calamba, specifically those taking basic calculus subjects, were the locale of the study. Stratified random sampling and purposive sampling were utilized. A total of 85 students were the respondents, whereas 10 students were the participants. Adapted and crafted instruments and interview guide questionnaires were applied for data collection. Statistical tools included frequency distribution, weighted mean, and paired t-test. Interpretative phenomenological analysis was used in the qualitative aspect. Findings revealed that the growth mindset approach significantly improved students' performance and attitudes toward basic calculus. There were notable similarities and differences in respondents' insights regarding the challenges and successes of implementing a growth mindset. A significant difference was found between pre-test and post test results before and after implementing growth mindset pedagogy. Qualitative themes included Personal Development and Growth Mindset, Approach to Knowledge Acquisition, Support Systems and Environment, Motivation for Learning Basic Calculus, Effective Teaching Methodology, Use of Formative Assessment, and Challenges in Implementation. As an output of the study, a learning material was proposed.